The use of the organic–inorganic hybrid polymer Al(OH)3–polyacrylamide to flocculate particles in the cyanide tailing suspensions. (April 2016) - Liu, Ya; Lv, Cuicui; Ding, Jian; Qian, Peng; Zhang, Xiaomeng; Yu, Yang; Ye, Shufeng; Chen, Yunfa
Graphical abstract: With the optimum dosage of 40 g/t, the initial settling rate (ISR) of particles was 11.7 m/h with Al45 –PAM, 18.5 times of the blank without flocculants. 98.2% of the turbidity was removed from the cyanide tailing suspensions. Highlights: At 40 g/t, the ISR of particles was 11.7 m/h with Al45 –PAM, 18.5 times of the blank. 98.2% of the turbidity was removed from the cyanide tailing suspension with Al45 –PAM. Charge neutralization and bridge adsorption plays vital roles in Al–PAM flocculation. Abstract: The organic–inorganic hybrid polymer Al(OH)3 –polyacrylamide (Al–PAM) was investigated in flocculation of particles in 10 wt% cyanide tailing suspensions in this study. The effect of Al–PAM was evaluated with photoelectric turbidimeter, focused beam reflectance measurement (FBRM) and particle video microscope (PVM). It was found that as the amount of Al45 –PAM with maximum zeta potential and molecular weight increased, the initial settling rate of particles increased, reaching the highest 11.7 m/h, 18.5 times of the blank without flocculants. Correspondingly, the turbidity of the supernatant was 0.95 NTU, compared to 291.6 NTU in the blank, which was over 98% of turbidity removal efficiency. The cationic Al–PAM demonstrated better flocculation to the particles in the cyanide tailing suspensions than the commercial non-ionic guar gum (GG), and has potential for commercialization .The electrostatic repulsion between tailing particles was regarded as a critical parameter in determining polymer flocculation and our study indicated that both charge neutralization and bridge adsorption contributed to the particle flocculation.